Direct foaming of macroporous ceramics containing colloidal alumina. Issue 11 (1st June 2021) - Finhana, I.C.; Machado, V.V.S.; Santos, T.; Borges, O.H.; Salvini, V.R.; Pandolfelli, V.C.
Abstract: Liquid foams containing Al2 O3 nanoparticles were obtained after direct foaming of a colloidal alumina suspension with ammonium stearate. These systems were stable for at least 24 h and were comprised by small cells (<35 μm). Up to 10 wt% of these foams were added to an ultrastable Al2 O3 -stabilised one and resulted in macroporous samples with high total porosity (>70%). Their green mechanical strength was proportional to the amount of colloidal alumina added, but lower than a composition with calcium aluminate cement. When compared with compositions prepared with colloidal alumina suspension, the colloidal foams resulted in samples with a higher number of small pores (<30 μm) and lower linear shrinkage after firing at 1600 °C for 5 h ( 9%). Thus, colloidal alumina foams can be used for processing macroporous refractory ceramics with smaller pores, lower dimensional changes after firing and higher porosity. Graphical abstract: Image 1